The Present and the Past in the Sagas of the Icelanders - Antonsson, HT (Proceedings of the British Academy, 2017)
This chapter examines how the Sagas of Icelanders (Íslendingasögur), which were mostly written in the thirteenth and fourteenth centuries, reected their present in a particularly period of the past, the socalled ‘Saga-Age’ which roughly covers the period between the Settlement of Iceland in the late ninth century to the second half of the eleventh century. Iceland’s peculiar constitutional arrangement during the Commonwealth period (930–1262/64), most notably the absence of kingship, freed authors from following a clearly demarcated narrative arch that focused on a single royal dynasty (as, for instance, in Denmark and Norway). Though predominantly concerned with disputes, saga writers could address issues of contemporary relevance, such as the nature of lordship and role of law, through stories set in a society similar, but not identical, to their own.